Optical coherence tomography identifies outer retina thinning in frontotemporal degeneration. (10th October 2017) - Kim, Benjamin J.; Irwin, David J.; Song, Delu; Daniel, Ebenezer; Leveque, Jennifer D.; Raquib, Aaishah R.; Pan, Wei; Ying, Gui-Shuang; Aleman, Tomas S.; Dunaief, Joshua L.; Grossman, Murray
Abstract : Objective: Whereas Alzheimer disease (AD) is associated with inner retina thinning visualized by spectral-domain optical coherence tomography (SD-OCT), we sought to determine if the retina has a distinguishing biomarker for frontotemporal degeneration (FTD). Methods: Using a cross-sectional design, we examined retinal structure in 38 consecutively enrolled patients with FTD and 44 controls using a standard SD-OCT protocol. Retinal layers were segmented with the Iowa Reference Algorithm. Subgroups of highly predictive molecular pathology (tauopathy, TAR DNA–binding protein 43, unknown) were determined by clinical criteria, genetic markers, and a CSF biomarker (total tau: β-amyloid) to exclude presumed AD. We excluded eyes with poor image quality or confounding diseases. SD-OCT measures of patients (n = 46 eyes) and controls (n = 69 eyes) were compared using a generalized linear model accounting for intereye correlation, and correlations between retinal layer thicknesses and Mini-Mental State Examination (MMSE) were evaluated. Results: Adjusting for age, sex, and race, patients with FTD had a thinner outer retina than controls (132 vs 142 μm, p = 0.004). Patients with FTD also had a thinner outer nuclear layer (ONL) (88.5 vs 97.9 μm, p = 0.003) and ellipsoid zone (EZ) (14.5 vs 15.1 μm, p = 0.009) than controls, but had similar thicknesses for inner retinal layers. The outer retina thickness of patients correlated with MMSE (Spearman r = 0.44, p = 0.03). The highly predictive tauopathy subgroup (n = 31 eyes) also had a thinner ONL (88.7 vs 97.4 μm, p = 0.01) and EZ (14.4 vs 15.1 μm, p = 0.01) than controls. Conclusions: FTD is associated with outer retina thinning, and this thinning correlates with disease severity.